The knowledge of high school students from the interior of the state of Amazonas about financial education (Research, Society and Development, 2023)
This study aimed to identify the level of knowledge about financial education among high school students from public schools, as well as their socioeconomic profile; consumption and saving habits; sources of information on the topic; the types of approach to financial education received by high school students in Tefé-Amazonas. The survey was carried out with 253 students from six schools through a printed questionnaire. Among the students interviewed, 52.6% were female, 43.1% male and 4.3% did not want to answer. Ages ranged from 15 to 24 years. As for the socioeconomic level, the majority declared a monthly family income of up to two minimum wages, with the mother as the person who contributed the most to the income. Most do not have any source of income from work or internship, receiving some money from their parents and generally being able to use it however they want. The habit of saving was present in most responses, but for less than half of them there is some money left over at the end of the month. The school was considered the largest source of information on financial education, followed by the internet. Regarding knowledge, students felt more secure when the topics addressed money, savings, investment, conscious consumption and classification of expenses. Lack of knowledge about the interest charged by credit card companies and insecurity about monetary correction can make respondents more susceptible to debt.